PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI DAN KINERJA PEGAWAI (Studi Pada Badan Pengembangan Sumberdaya Manusia Provinsi Maluku) - Titioka, Baretha Meisar; Siahainenia, Astrid J.D. (FEB Universitas Sam Ratulangi Manado, 2019)
This study aims to discuss the leadership style and organizational culture of organizational commitment and performance at the Maluku Provincial Human Resources Development Agency. The population of this study was 65 Civil Servants in the Maluku Province Education and Training Agency. The collected data analyzed using descriptive statistics and inferential statistics through Partial Least Square (PLS) analysis. The results showed that the leadership style variable had a positive and significant effect on organizational commitment. The influence of organizational culture on organizational commitment is positive. The influence of leadership style on employee performance is positive and significant. Positive and significant organizational performance on employee performance and positive and significant organizational commitment to employee performance. To get the expected employee improvement within the Maluku Provincial Human Resources Development Agency improve its leadership style and organizational culture so that the organizational commitment increases and increases in employee needsKeywords: Leadership Style, Organization Culture, Organization Commitment, Employee Performance